ANALISIS KEPUASAN KERJA KARYAWAN TERHADAP KEBIJAKAN MANAJEMEN DI RSUD GENTENG BANYUWANGI - Yoelianita, Betty Erda; Wirawati, Wahyu Adri; Roshanti, Dian (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2025)
Human Resources (HR), especially hospital employees, are an important and crucial component in hospital services, hence hospitals should carry out a mechanism to maintain human resources by paying attention to employee job satisfaction and evaluating employee performance to improve optimal hospital services and quality. This research aimed to determine the level of employee satisfaction in management and management policies in RSUD Genteng. The study was performed on March to May 2024. The population were 409 employees with 200 samples. Based on the results of research, the score of employee satisfaction on management policies in RSUD Genteng Banyuwangi was 83.403. It showed the employees were satisfied and the quality was B. The study consisted of 8 elements, and each showed result as follows (1) Hospital plan element obtained a score of 83.00 showing that the employees were satisfied (quality B); (2) Elements of organizational behavior towards employees obtained 82.75 showing the employees were satisfied (quality B); (3) Work issue element obtained 85.14 showing the employees were satisfied (quality B); (4) Management element obtained 82.87 showing the employees were satisfied (quality B); (5) Supervision issue elements obtained 83.47 showing the employees were satisfied (quality B); (6) Elements of HR maintenance and development issues obtained 83.37 showing the employees were satisfied (quality B); (7) Elements of compensation issues and benefits received by employees obtained 83.75 showing the employees were satisfied (quality B); (8) Performance issue elements obtained 82.85 showing the employees were satisfied (quality B).